Book review of: Allmendinger, P.; Tewdwr-Jones, M.; Wargent, M. (eds.) (2025): Critical Planning Futures. New Directions in Planning Theory - Mäntysalo, Raine (Raumforschung und Raumordnung | Spatial Research and Planning, 2026)
Book review.